L2-L1 Translation Priming Effects in a Lexical Decision Task: Evidence From Low Proficient Korean-English Bilinguals - Lee, Yoonhyoung; Jang, Euna; Choi, Wonil (Frontiers in Psychology, 2018)
One of the key issues in bilingual lexical representation is whether L1 processing is facilitated by L2 words. In this study, we conducted two experiments using the masked priming paradigm to examine how L2-L1 translation priming effects emerges when unbalanced, low proficiency, Korean-English bilinguals performed a lexical decision task. In Experiment 1, we used a 150 ms Stimulus Onset Asynchrony (hereafter, SOA) (50 ms prime duration followed by 100 ms blank) and found a significant L2-L1 translation priming effect. In contrast, in Experiment 2, we used a 60 ms SOA (50 ms prime duration followed by 10 ms blank) and found a null effect of L2-L1 translation priming. This finding is the first demonstration of a significant L2-L1 translation priming effect with unbalanced Korean-English bilinguals. The pattern of results reported in the present study is discussed based on bilingual word recognition models.